MENUMBUHKAN GENERASI BERKARAKTER: PERAN STRATEGIS KURIKULUM MERDEKA DALAM MEMBANGUN AKHLAK TERPUJI MELALUI PENDIDIKAN KARAKTER - Imroatis Syarifah, Hasnia; Azzahra, Fatimah; Nadzifah Hasanah, Naurah; Imamul Muttaqin, M. (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
Character education is a component of the independent curriculum that tries to mould character and is related to the moral conundrums that today's youngsters are facing. Naturally. These issues are quite worrying, particularly in view of the way that national education is forming the country's identity. This study made use of library research, which collects written data from books and specialised publications. Therefore, the goal of this study is to determine how urgently the autonomous curriculum needs to promote morally admirable values through character education. What is the significance of having a stand-alone character education programme, and how might honourable ideals be attained through it? is how the problem of the study was phrased. As a result of this study, The policy of acting in accordance with Pancasila values and nurturing admirable morals via characteristics is guided by the independent curriculum. To promote character education, society, the environment, parents, and educators must all set a good example of behaviour. Character education can be applied in a variety of ways within school walls to assist kids in developing positive attributes. Creating an activity programme that aids in pupils' acquisition of moral principles is one such method.